Angiotensin II during Experimentally Simulated Central Hypovolemia - Jensen, Theo Walther; Olsen, Niels Vidiendal (Frontiers in Cardiovascular Medicine, 2016)
Abstract: Central hypovolemia, defined as diminished blood volume in the heart and pulmonary vascular bed, is still an unresolved problem from a therapeutic point of view. The development of pharmaceutical agents targeted at specific angiotensin II receptors, like the non-peptidergic AT2-receptor agonist compound 21, is yielding many opportunities to uncover more knowledge about angiotensin II receptor profiles and possible therapeutic use. Cardiovascular, anti-inflammatory and neuroprotective therapeutic use of compound 21 have been suggested. However, there has not yet been a focus on the use of these agents in a hypovolemic setting. We argue that the latest debates on the effect of angiotensin II during hypovolemia might guide for future studies investigating the effect of such agents during experimentally simulated central hypovolemia. The purpose of this review is to examine the role of angiotensin II during episodes of central hypovolemia. To examine this, we reviewed results from studies with three experimental models of simulated hypovolemia: head up tilt table test, lower body negative pressure, and hemorrhage of animals. A systemic literature search was made with the use of PubMed/MEDLINE for studies that measured variables of the renin-angiotensin system or its effect during simulated hypovolemia. 12 articles, using one of the three models, were included and showed a possible organ protective effect and an effect on the sympathetic system of angiotensin II during hypovolemia. The results support the possible organ protective vasodilatory role for the AT2-receptor during hypovolemia on both the kidney and the splanchnic tissue.